2020
DOI: 10.1111/cts.12879
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SLCO1B1 Polymorphisms on High‐Dose Methotrexate Clearance in Children and Young Adults With Leukemia and Lymphoblastic Lymphoma

Abstract: High-dose (HD) methotrexate (MTX) is a critical component of treatment for hematologic malignancies in children and young adults. Therapeutic drug monitoring is necessary due to substantial interindividual variation in MTX clearance. Common function-altering polymorphisms in SLCO1B1 (encodes OATP1B1, which transports MTX) may contribute to clearance variability. We performed pharmacokinetic modeling using data for 106 children and young adults treated with HD MTX for hematologic malignancies; of 396 total cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 37 publications
0
19
0
5
Order By: Relevance
“…The SNP most often tested for association with MTX PK measures is rs4149056, which encodes a T521C transition that reduces the localization of the transporter to the surface of the cell and causes a severe reduction in transport of MTX in vitro [ 64 ]. This variant was universally associated with decreased MTX clearance among all the studies included in this review [ 21 , 22 , 27 , 28 , 32 , 33 , 34 , 35 , 38 , 43 , 49 , 50 , 51 , 52 , 54 , 55 ]. The rs4149056 common variant is included in two * alleles, the no function *5 (no other coding variants) allele and the more common *15 (with rs2306283 A > G) allele.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The SNP most often tested for association with MTX PK measures is rs4149056, which encodes a T521C transition that reduces the localization of the transporter to the surface of the cell and causes a severe reduction in transport of MTX in vitro [ 64 ]. This variant was universally associated with decreased MTX clearance among all the studies included in this review [ 21 , 22 , 27 , 28 , 32 , 33 , 34 , 35 , 38 , 43 , 49 , 50 , 51 , 52 , 54 , 55 ]. The rs4149056 common variant is included in two * alleles, the no function *5 (no other coding variants) allele and the more common *15 (with rs2306283 A > G) allele.…”
Section: Resultsmentioning
confidence: 99%
“…The rs2306283 A > G variant is included in many * alleles, and is associated with increased transporter expression. Most studies found that this SNP associated with faster MTX clearance [ 33 , 54 ], but one found that it associated with slower clearance [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is metabolized to 7-hydroxy-MTX in the liver, which contributes to MTX activity (Csordas et al, 2013), and a small part of MTX is excreted in the bile with partial intestinal reabsorption. Several efflux and uptake transporters (e.g., BCRP, MRP2, MRP3, MRP4, OAT1, and OAT3) are involved in the pharmacokinetic (PK) disposition process of MTX, which could lead to substantial variability in PK exposure (Treviño et al, 2009;Leveque et al, 2011;Ramsey et al, 2013;Schulte et al, 2021). Recent studies suggested that MTX elimination varied significantly between HD-MTX courses, and extremely delayed MTX elimination was observed in approximately 0.5% of pediatric patients with ALL (Svahn et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Множество транспортеров и ферментов участвуют в метаболизме фолиевой кислоты, а другие обеспечивают всасывание и транспорт МТХ, что влияет на ФК МТХ. Активность белков-транспортеров оказы-вает влияние на концентрации препаратов в плазме крови и тканях, тем самым определяя лекарственную токсичность [5,9,10]. Выявление наличия полиморфизмов генов, кодирующих белки-переносчики МТХ и ферменты его биотрансформации, позволяет прогнозировать риск МТХ-индуцированной токсичности со стороны кожи и слизистых, печени, почек, нервной системы [2,6].…”
Section: метотрексатunclassified